Development of Image Recognition for Underwater Vehicle Applications - Syed Abdul Hamid , Syed Mohamad Shazali; Mohd Aras, Mohd Shahrieel; Ali, Fara Ashikin; Anuar , Mohamed Kassim; Abdul Azis, Fadilah (2011)
This project focuses on development of algorithm for image recognition of images from vision system for underwater vehicle applications. The main objective of this project is to develop algorithm from vision system sensor for Deep Submergence Vehicle (DSV) applications which have high performance automated detection and monitoring cracks on anchored ship at its port/dock as well as moving ship. It is also expected to recognize biological underwater object to support on deck auto monitoring system. The developed algorithm will be used to recognize relevant underwater object or living thing. This paper will discuss the experimental setup as well as the prior algorithm which will be used for this research. The approach that had been used to imitate the underwater world will be presented as well as related issues on underwater vision technology. This paper also discusses the expected result of this research and potential application of the developed algorithm.